THE INFLUENCE OF COMPENSATION, JOB STRESS AND COMMUNICATION ON EMPLOYEE PERFORMANCE IN TAX MANAGEMENT AGENCY AND REGIONAL LEVIES MEDAN CITY - Fauziah, Fauziah; Iskandar, Dani (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine and analyze the effect of compensation on employee performance at the Medan City Regional Tax and Levy Management Agency, to determine and analyze the influence of work stress on employee performance at the Medan City Regional Tax and Levy Management Agency, to determine and analyze the effect of communication on employee performance at the Medan City Regional Tax and Levy Management Agency and to determine and analyze the influence of communication, work stress and communication on employee performance at the Medan City Regional Tax and Levy Management Agency. In this research the author used a quantitative data approach. The population of this study was all employees at the Medan City Regional Tax and Retribution Management Agency, totaling 575 people. Determining the number of samples taken as respondents using the Sovlin formula , the sample in this study was 85 employees of the Medan City Regional Tax and Levy Management Agency. Data collection techniques in this research are interviews , documentation studies and questionnaires. Meanwhile, the data analysis technique used is multiple linear regression, with classical assumptions. The individual test results show that there is a significant positive influence between compensation on Performance. There is a significant positive influence between work stress and performance. The results of individual testing show the influence of communication on performance. Meanwhile, simultaneously there is an influence of compensation, work stress and communication on performance.